Impact of fungicide mode of action and application timing on the control of Mycosphaerella graminicola and the physiology and yield of wheat - Quintero Palomar, Maria Angelica; Justus Liebig University Giessen (My University, 2014)
Septoria leaf blotch is a devastating wheat fungal disease caused by the fungus Mycosphaerella graminicola that, under severe epidemics, can cause up to 60% yield loss. Even though resistant varieties do exist, the possibility that M. graminicola will overcome resistant varieties is very high due to its genetic diversity and rapid evolution upon selection pressure. M. graminicola control is therefore, heavily dependent on fungicide treatment. Modern agrochemicals compounds with varying modes of action are successful in controlling a wide variety of fungal diseases that threaten crop yield potential. Nonetheless, in order to provide the most appropriate protection and, hence, secure crop productivity, appropriate application timing is of great importance. For this reason, the present study aimed at evaluating the effects of application timing and mode of action of the Pyraclostrobin, Epoxiconazole and Fluxapyroxad fungicides on controlling septoria leaf blotch and the corresponding development of wheat yield. Three different experimental setups were tested, ranging from controlled conditions in a glasshouse, semi-control conditions in micro-plots to natural growth environments in the field. Firstly, by employing molecular biology techniques such as quantitative real time PCR (qPCR) and microarray DNA chips, it could be demonstrated that preventative fungicide application not only provides the most appropriate disease control, it also avoids the activation of costly defense responses that would have a negative impact on wheat yield. Furthermore, changes in plant hormone metabolism, which may have additional impacts on plant growth and development, after the application of Pyraclostrobin, Epoxiconazole and Fluxapyroxad under disease pressure and disease-free conditions, were observed. Additionally, a transient induction of photosynthesis- and energy-related genes after the preventative application of the cellular respiration inhibitors Pyraclostrobin and Fluxapyroxad was also observed. Based on these results, yield trials under semi-controlled and natural conditions were carried out in order to evaluate if higher yields would be obtained when a product is sprayed preventatively, thereby avoiding the activation of plant defense responses, than when applied after the infection has already occurred. Even though no significant differences between the application timings could be identified due to the high variability of the data, a tendency for higher yields were detected in the micro-plot trials under semi-natural conditions after the preventative application of Pyraclostrobin and Fluxapyroxad. These results could not be transferred to the field, however, most likely due to the fact that in nature deciding the point of time at which a preventative application is needed is more complicated as M. graminicola infection occurs throughout the growing season. Nonetheless, it could be demonstrated that an approximately 20% yield increase can be obtained by performing a single fungicide application to treat the septoria leaf blotch disease in wheat.

Septoria-Blattdürre gehört zu einer der bedeutendsten Pilzkrankheiten im Weizenbau Nord-West-Europas. Die Krankheit wird durch den Pilz Mycosphaerella graminicola verursacht. Bei für den Pilz günstigen Umweltbedingungen können Ertragsverluste von bis zu 60% entstehen. Obwohl Weizensorten mit Resistenzen gegen Septoria-Blattdürre im Markt weit verbreitet sind, ist chemischer Pflanzenschutz zur Kontrolle der Krankheit unverzichtbar. Moderne Fungizide unterschiedlicher Wirkmechanismen können die Pilzkrankheit sehr erfolgreich bekämpfen und Erträge sichern. Zielsetzung dieser Arbeit war es zu untersuchen, welchen Einfluss der Zeitpunkt der Applikation (protektiv oder kurativ) sowie die unterschiedlichen Wirkmechanismen der drei fungiziden Wirkstoffe Pyraclostrobin, Epoxiconazole und Fluxapyroxad auf die Entwicklung von Septoria-Blattdürre und letzten Endes den Ertrag im Weizen haben.Die Fragestellung wurde anhand drei verschiedener Versuchseinstellungen, die von kontrollierten- über semi-kontrollierte- bis hin zu Freilandbedingungen reichten. Unter kontrollierten Versuchsbedingungen im voll klimatisierten Gewächshaus wurden Proben genommen und mit Hilfe von quantitativer real-time PCR (qPCR) und Microarray Technologien untersucht. Anhand dieser Versuchseinstellungen und Messmethoden konnte gezeigt werden, dass die protektive Applikation eines die Sporenkeimung hemmenden Fungizids die Pflanze nicht nur effektiv vor einer Infektion mit M. graminicola schützt, sondern auch die Aktivierung der pflanzlichen Abwehr verhindert. Desweiteren konnten Veränderungen im Phytohormonhaushalt nach Applikation der Fungizide sowohl nach Infektion des Erregers als auch unter befallsfreien Bedingungen festgestellt werden. Bei Pflanzen, die präventiv mit Pyraclostrobin und Fluxapyroxad behandelt wurden, konnte darüber hinaus eine vorübergehende Hochregulation von Genen der Photosynthese und des Energiehaushaltes gezeigt werden. Mögliche positive und negative Effekte der gefunden Veränderungen der phytohormon-, phytosynthese- sowie energiebezogenen Gene werden im Kontext des aktuellen Stand des Wissens diskutiert.In Versuchen semi-kontrollierten sowie unter Freilandbedingungen sollte geprüft werden, ob sich die unter kontrollierten Bedingungen gefunden Effekte im Ertrag widerspiegeln. Aufgrund der hohen biologischen Varianz gelang es nicht, statistisch signifikante Unterschiede nachzuweisen. Lediglich bis zu 20 % höhere Erträge gegenüber den unbehandelten Kontrollen konnten bei mit M. graminicola infiziertem Weizen statistisch abgesichert werden.
Einfluss von Fungizid-Wirkmechanismen und Zeitpunkt der Applikation auf die Entwicklung von Mycosphaerella graminicola und den Ertrag im Weizen
Keywords: Fungizid; Weizen; Ertrag; Mycosphaerella graminicola; Microarrays; fungicides; wheat; yield; Mycosphaerella graminicola; microarrays; ddc:580